2016
DOI: 10.1038/bjc.2016.172
|View full text |Cite
|
Sign up to set email alerts
|

CXCL9 and CXCL10 predict survival and are regulated by cyclooxygenase inhibition in advanced serous ovarian cancer

Abstract: Background:Tumour-infiltrating lymphocytes (TILs) are associated with improved survival in several epithelial cancers. The two chemokines CXCL9 and CXCL10 facilitate chemotactic recruitment of TILs, and their intratumoral accumulation is a conceivable way to improve TIL-dependent immune intervention in cancer. However, the prognostic impact of CXCL9 and CXCL10 in high-grade serous ovarian cancer (HGSC) is largely unknown.Methods:One hundred and eighty four cases of HGSC were immunohistochemically analyzed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
175
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(201 citation statements)
references
References 48 publications
(70 reference statements)
14
175
2
5
Order By: Relevance
“…CXCL9 and CXCL10 are chemokines that bind to CXCR3 leading to the recruitment of tumor‐suppressive T cells and NK cells into tumor stroma . Higher concentrations of these chemokines in tumors is associated with a higher lymphocyte infiltration and better overall survival in ovarian and other cancers . In contrast, other studies have suggested a protumorigenic role of these two chemokines in cancer progression and metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…CXCL9 and CXCL10 are chemokines that bind to CXCR3 leading to the recruitment of tumor‐suppressive T cells and NK cells into tumor stroma . Higher concentrations of these chemokines in tumors is associated with a higher lymphocyte infiltration and better overall survival in ovarian and other cancers . In contrast, other studies have suggested a protumorigenic role of these two chemokines in cancer progression and metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…14 Detailed patient characteristics are given in Table 1. All patients underwent standard debulking surgery followed by platinum-based chemotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, it has been widely reported that a higher density of TILs, such as T and B lymphocytes, is associated with increased overall survival and chemo-radiosensitivity in OC [121][122][123][124]. Previous reports have confirmed that higher levels of the cytokines IL-6 and VEGF are associated with chemoresistance, are both markers for poor prognosis in OC and exhibit pro-tumorigenic effects, such as promoting angiogenesis [125,126]. These studies highlight key insights that are applicable to both basic OC research and to the prevention and treatment of OC.…”
Section: Immunosuppressive Mechanisms and Chronic Inflammationmentioning
confidence: 97%